ANALISIS YURIDIS PERBUATAN PENYUAPAN DALAM TINDAK PIDANA KORUPSI - Hasibuan, Imelda; Sunariyo (The Juris, 2023)
Over time, discussions about corruption have never ceased; corruption in Indonesia is rising. Corruption has spread widely in society in terms of the number of cases and the amount of state losses. It is a criminal act of exceptional quality, penetrating all aspects of community life. Examined from a juridical perspective, corruption is an extraordinary crime. Uncontrolled corruption will bring disaster not only to the nation's life but also to the nation and the state. The enforcement of Co Crimes law (Law Number 20 of 2001 amending Law No. 31 of 1999 concerning the Eradication of Corruption Crimes) is the primary remedy (preferred means), and criminal sanctions are the primary choice (premium medium). The results of this research show that the judge's decision is considered incorrect because the decision is proven to involve bribery as stated in Article 11 of Law Number 20 of 2001, amending Law No. 31 of 1999 concerning the Eradication of Corruption Crimes against the perpetrator mentioned, Jamel Panjaitan. Even though legal considerations and witness statements confirm that the perpetrator committed the crime of corruption through extortion as regulated in Article 12 letter e of Law Number 20 of 2001 amending Law No. 31 of 1999 concerning the Eradication of Corruption Crimes. Moreover, if the perpetrator's actions involve bribery, the briber should also be punished.